Ultrastructural examination of mouse kidney glomerular capillary loop by sandwich freezing and freeze-substitution. (2nd July 2022) - Yamaguchi, Masashi; Takahashi-Nakaguchi, Azusa; Uematsu, Katsuyuki; Yamada, Hiroyuki; Sato-Okamoto, Michiyo; Chibana, Hiroji
Abstract: Sandwich freezing is a method of rapid freezing by sandwiching specimens between two metal disks and has been used for observing exquisite the close-to-native ultrastructure of living yeast and bacteria. Recently, this method has been found to be useful for preserving cell images of glutaraldehyde-fixed animal and human tissues. In the present study, this method was applied to observe the fine structure of mouse glomerular capillary loops. Morphometry was then performed, and the results were compared with the data obtained by an in vivo cryotechnique, which may provide the closest ultrastructure to the native state of living tissue. The results show that the ultrastructure of glomerular capillary loops obtained by sandwich freezing–freeze-substitution after glutaraldehyde fixation was close to that of the ultrastructure obtained by in vivo cryotechnique not only in the quality of cell image but also in quantitative morphometry. They indicate that the ultrastructure obtained by sandwich freezing–freeze-substitution after glutaraldehyde fixation may more closely reflect the living state of cells and tissues than conventional chemical fixation and dehydration at room temperature and conventional rapid freezing–freeze-substitution of excised tissues without glutaraldehyde fixation. Sandwich freezing–freeze-substitution techniques should be used routinely as a standard method for observing the close-to-native ultrastructure of biological specimens.